Early atmospheric detection of carbon dioxide from carbon capture and storage sites. (2nd August 2016) - Pak, Nasrin Mostafavi; Rempillo, Ofelia; Norman, Ann-Lise; Layzell, David B.
ABSTRACT: The early atmospheric detection of carbon dioxide (CO2 ) leaks from carbon capture and storage (CCS) sites is important both to inform remediation efforts and to build and maintain public support for CCS in mitigating greenhouse gas emissions. A gas analysis system was developed to assess the origin of plumes of air enriched in CO2, as to whether CO2 is from a CCS site or from the oxidation of carbon compounds. The system measured CO2 and O2 concentrations for different plume samples relative to background air and calculated the gas differential concentration ratio (GDCR = −ΔO2 /ΔCO2 ). The experimental results were in good agreement with theoretical calculations that placed GDCR values for a CO2 leak at 0.21, compared with GDCR values of 1–1.8 for the combustion of carbon compounds. Although some combustion plume samples deviated in GDCR from theoretical, the very low GDCR values associated with plumes from CO2 leaks provided confidence that this technology holds promise in providing a tool for the early detection of CO2 leaks from CCS sites.   Implications : This work contributes to the development of a cost-effective technology for the early detection of leaks from sites where CO2 has been injected into the subsurface to enhance oil recovery or to permanently store the gas as a strategy for mitigating climate change. Such technology will be important in building public confidence regarding the safety and security of carbon capture and storage sites.